A rGO–DNAzyme assisted fluorescence method for sensitive RNase A activity assay and natural compound screening. Issue 37 (2nd September 2021) - Qin, Yan; Long, Ying; Zhou, Ting; Luo, Ruxin; Tong, Chunyi; Xie, Qian; Wang, Wei; Liu, Bin
Abstract : As a key regulator of human physiology and metabolic processes, ribonuclease (RNase) A can be used as an important biomarker for predicting human disease occurrence. Abstract : As a key regulator of human physiology and metabolic processes, ribonuclease (RNase) A can be used as an important biomarker for predicting human disease occurrence. Hence, establishing sensitive methods for tracking RNase A activity in vitro and in living cells is of great importance. Herein, we present a convenient fluorescence method assisted by reduced graphene oxide (rGO) and DNAzyme mediated fluorescence signal release for RNase A assay. The fluorescence change of the new method showed a positive linear relation with RNase A concentration in the range from 0.5 pg μL −1 to 1 ng μL −1 with a detection limit of 0.089 pg μL −1 . By using this method to screen the effector of RNase A from natural compounds, the natural compound of B6 was found to stimulate RNase A activity in vitro and in vivo, the result of which was supported by the real-time imaging of RNase A in living cells. In summary, this fluorescence method with high sensitivity and specificity provides an alternative for RNase A activity assay and effector screening.